2004
DOI: 10.1007/s00011-004-1307-8
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil recruitment in mast cell-dependent inflammation: inhibitory mechanisms of glucocorticoids

Abstract: Mast cells are strategically localized along the microvasculature in tissues in close contact with the external environment, such as the skin, lung and intestines. By releasing a multi-faceted spectrum of proinflammatory mediators, such as cytokines and chemokines, mast cells have the capacity to coordinate trafficking of leukocytes. Mast cells play a pathophysiological role in numerous inflammatory diseases as diverse as hypersensitivity reactions, ischemia/reperfusion injury and rheumatoid arthritis. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 89 publications
2
42
0
Order By: Relevance
“…Neutrophils were shown to express GR and ER receptor, suggesting a potential role of these receptors in the regulation of neutrophil function (Molero et al, 2002). Other studies have also demonstrated that GR may modulate leukocyte-endothelial cell interactions during inflammation through regulation of endothelial adhesion molecules (Schramm and Thorlacius, 2004). Furthermore, we found that the tissue damage induced by carrageenan was associated with high levels of the tissue thiobarbituric acid-reactant MDA, which is considered a good indicator of lipid peroxidation (Eiserich et al, 1996).…”
Section: Cross-talk Between Gr and Er In A Model Of Inflammation 139mentioning
confidence: 52%
“…Neutrophils were shown to express GR and ER receptor, suggesting a potential role of these receptors in the regulation of neutrophil function (Molero et al, 2002). Other studies have also demonstrated that GR may modulate leukocyte-endothelial cell interactions during inflammation through regulation of endothelial adhesion molecules (Schramm and Thorlacius, 2004). Furthermore, we found that the tissue damage induced by carrageenan was associated with high levels of the tissue thiobarbituric acid-reactant MDA, which is considered a good indicator of lipid peroxidation (Eiserich et al, 1996).…”
Section: Cross-talk Between Gr and Er In A Model Of Inflammation 139mentioning
confidence: 52%
“…Prevention of granulocyte transmigration is one of the mechanisms by which GCs exert their anti-inflammatory action (36,37). We have shown here that GILZ is necessary for GC-induced inhibition of neutrophil migration into sites of inflammation.…”
Section: Discussionmentioning
confidence: 63%
“…Lindestrom and his colleagues [4] found the eosinophils and mast cells in rat ileum gradually increased after intestine ischemia (60 min)/reperfusion (60 min), and reported that the epithelium permeability increased significantly after ischemia-reperfusion. The researches of Kanwar and Schramm [5,6] were focused on mast cells stimulating neutrophil adherence, resupination, recruitment, and the intestinal mucosal injury. Boros [7] reported that mast cell degranulation prior to ischemia may induce a potentially protective mechanism in the small bowel mucosa and decrease ischemia-reperfusion injury in the dog.…”
Section: Introductionmentioning
confidence: 99%